TRADISI BASIACUONG DI KAMPAR RIAU - Tarekh Muhammad Iqbal; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research examines the Basiacuong Tradition in Kampar Riau. culture is an inseparable part of the civilization of a region, thetradition basiacuong is the proverbial language used by the Kampar community in general in various traditional events. Thetradition basiacuonghas been known for a long time in the community so that its formation patterns are always passed on from generation to generation. thetradition basiacuong has special values that are considered in the community, generally the values become a reference for community guidelines in behaving and behaving. In the research process, the researcher examines the connectedness of the community in viewing and seeing thetradition basiacuong and the system inside the basiacuong. The researcher used the theory of symbolic interaction. The research method used is descriptive qualitative method with 13 research subjects consisting of tribal ninik mamak and village youth. The results of this study indicate that the traditionaltradition basiacuong has a special value that is seen in the community so that the community has a standard value in viewing the traditionaltradition basiacuong. Furthermore, the words basiacuong are symbols used in the social interactions of the Riau Kampar community Keywords: Tradition, Basiacuong, Symbol